PENINGKATAN LITERASI MEMBACA SISWA MELALUI MODEL IPAER (IDENTIFYING PLANNING ACTING EVALUATING REFLECTING) DI SEKOLAH DASAR - Lestari, Intan; Nayariah Siregar; Fitri Nauli Siagian (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the low reading literacy skills of fourth-grade students in Civic Education learning, particularly in understanding reading texts, identifying main ideas, and drawing conclusions from texts. The aim of this study was to improve students’ reading literacy skills through the implementation of the IPAER learning model (Identifying, Planning, Acting, Evaluating, Reflecting). To address this problem, the research employed Classroom Action Research (CAR) using the Kemmis and McTaggart model, which was conducted in three cycles with 29 students as research subjects. The results showed a significant improvement in students’ reading literacy skills, where the average score increased from 36.42% with a mastery level of 6.90% (2 students) in the pre-cycle to 51.07% with 20.69% mastery (6 students) in Cycle I, then increased to 75.43% with 58.62% mastery (17 students) in Cycle II, and reached 93.97% with 100% mastery (29 students) in Cycle III. Based on these findings, it can be concluded that the IPAER learning model is effective in improving students’ reading literacy skills through active, meaningful, and student-centered learning.Keywords: Reading literacy; Civic Education; IPAER model; Classroom Action Research (CAR).